Modeling the re-anchoring of a ruptured tendon in bonded post-tensioned concrete - Abdelatif, Amged O.; Owen, John S.; Hussein, Mohammed F.M. (2012)
: In this study, a theoretical model is deve loped to simulate the re-anchorage of a ruptured bonded post-tensioning tendon. This includes estimating the re-anchorage length and stress distribution over the tendon. The model accounts for equilibrium and compatibility conditions at the steel-grout, grout-duct and duct-concrete interfaces as well as the effect of axial stresses in the strand and its confining materials, i.e. grout, duct and concrete. Formulation of the model is based on the elastic theory of thick-wall cylinders and the Coulomb friction model. The model has been validated against an axi-symmetrical Finite Element (FE) model, the UK Highway Agency’s BA51/95 model and previous experimental data. The models had been compared with the UK Highway Agency’s BA51/95 model and previous experimental data.